Fandom : identities and communities in a mediated world - Sandvoss, Cornel; Gray, Jonathan; Harrington, C. Lee (New York New York University Press, 2017)
We are all fans. Whether we log on to Web sites to scrutinize the latest plot turns in Lost, “stalk” our favorite celebrities on Gawker, attend gaming conventions, or simply wait with bated breath for the newest Harry Potter novel?each of us is a fan. Fandom extends beyond television and film to literature, opera, sports, and pop music, and encompasses both high and low culture.<U+000d><U+000a><U+000d><U+000a>Fandom brings together leading scholars to examine fans, their practices, and their favorite texts. This unparalleled selection of original essays examines instances across the spectrum of modern cultural consumption from Karl Marx to Paris Hilton, Buffy the Vampire Slayer to backyard wrestling, Bach fugues to Bollywood cinema? and nineteenth-century concert halls to computer gaming. Contributors examine fans of high cultural texts and genres, the spaces of fandom, fandom around the globe, the impact of new technologies on fandom, and the legal and historical contexts of fan activity. Fandom is key to understanding modern life in our increasingly mediated and globalized world.
Bibliografía: p. 365-391
Keywords: Cultura de masas; Medios de comunicación social -- Influencia; Cultura -- Aspectos sociológicos; Fans (Personas)